Exploring the OIC food manufacturer intention towards adopting Malaysian halal certification - Abdul Rahman, Rozailin; Mohamed, Zainal Abidin; Rezai, Golnaz; Shamsudin, Mad Nasir; Sharifuddin, Juwaidah (Science Publications, 2014)
Halal refers to the Islamic processing methods which places a great value on respect for the individuals and also the society. Currently, there are about 1.5 billion Muslims around the world and people from diverse races and religions are looking for cleaner and purer foods. There is no one set of standards as reference or any in the development phase for Halal certification in the Muslim world. Each country has its own Halal standards and regulations for Halal certification of manufactured food products. This phenomenon has attracted some of the food manufacturers to seek standardization of Halal certification. Malaysian Halal certification is now among the most widely recognized and respected symbols of Halal compliance in the world. Malaysia as a member of the Organization of the Islamic Conference (OIC) has aspirations of having their Halal logo adopted as the internationally recognized and accepted Halal certification especially among the member states. This study aims to understand the determinants that influence the OIC food manufacturers’ intention to adopt Malaysian Halal logo as the globally accepted Halal certificate through the application of an extended Theory of Planned Behaviour (TPB). Three hundred (300) OIC food manufacturers were interviewed. Structural Equation Model was used to assess the direct relationship between attitude, perceived behavioural control and subjective norms towards the food manufacturers’ intention to adopt Malaysia Halal logo as the International Halal Certification. The study found that perceived behavioural control is an important influential factor in creating the intention to adopt Malaysian Halal certification. Moreover, attitude is an important mediator for the OIC food manufacturers to have the intention to adopt Malaysian Halal certification.